The GLP-1 analog liraglutide attenuates acute liver injury in mice - Milani, Letícia; Galindo, Claudia M.; Turin de Oliveira, Natalia Mulinari; Corso, Claudia Rita; Adami, Eliana Rezende; Stipp, Maria Carolina; Beltrame, Olair Carlos; Acco, Alexandra (Annals of hepatology, 2019)
Acute liver injury is a current health problem with few effective treatments. The present study investigated the hepatoprotective and curative potential of the glucagon-like peptide-1 analog liraglutide against carbon tetrachloride (CCl4)-induced hepatotoxicity. Male Swiss mice were subjected to two protocols. The first protocol (Pretreatment) consisted of intraperitoneal (i.p.) treatment with liraglutide (0.057 and 0.118mgkg−1) or vehicle (distilled water) once daily for 7 days. On days 6 and 7, the animals were challenged with 2% CCl4 (5mgkg−1, i.p.). The second protocol (Late treatment) began with an injection of 5% CCl4 (5mgkg−1, i.p.) and subsequent treatment with liraglutide (0.057mgkg−1) or vehicle (distilled water) for 1 day. In both protocols, 24h after the last administration, blood and bile were collected from anesthetized animals, followed by euthanasia and liver collection. Plasma and bile underwent biochemical analyses, and histological, oxidative stress, and metabolic parameters were evaluated in the liver. Both liraglutide treatment protocols attenuated hepatotoxicity that was induced by CCl4, decreasing plasma levels of hepatic enzymes, stimulating the hepatic antioxidant system, and decreasing centrilobular necrosis, hepatic glycogen, and lipid accumulation. CCl4 tended to reduce bile lipid excretion, but liraglutide did not influence this parameter. The present results demonstrated the hepatoprotective and therapeutic effects of liraglutide, which may be attributable to a decrease in liver oxidative stress and the preservation of metabolism. Liraglutide may have potential as a complementary therapy for acute liver injury.